2020
DOI: 10.26434/chemrxiv.11900262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Efficient Synthesis of Tenofovir (PMPA): A Key Intermediate Leading to Tenofovir-Based HIV Medicines

Abstract: <p>Abstract: Herein, we report further improvements to the synthesis of tenofovir <b>1</b>, the precursor to tenofovir disoproxil fumarate and tenofovir alafenamide fumarate. Starting from acyclic precursor diaminomalononitrile <b>12</b>, a four-step protocol to tenofovir <b>1 </b>will allow for vertical integration for more manufacturers. The key transformation is a more convergent one step procedure from <b>6</b> as compared to the current comm… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…At 60 °C, dealkylation was already complete after 2 h. The pH was adjusted to 2.8–3.0 with NaOH solution to precipitate PMPA·H 2 O, which was dried afterward, as described in the literature. 10 On a 1 g scale, the conversion of HPA was slightly higher when using 1.7 equiv of 14 instead 1.5 equiv, while the isolated yields were similar (64 and 65%, respectively, Table 5 , entries 1 and 2). Despite the high conversions of HPA, large amounts of PMPA·H 2 O did not precipitate and remained in the mother liquor.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…At 60 °C, dealkylation was already complete after 2 h. The pH was adjusted to 2.8–3.0 with NaOH solution to precipitate PMPA·H 2 O, which was dried afterward, as described in the literature. 10 On a 1 g scale, the conversion of HPA was slightly higher when using 1.7 equiv of 14 instead 1.5 equiv, while the isolated yields were similar (64 and 65%, respectively, Table 5 , entries 1 and 2). Despite the high conversions of HPA, large amounts of PMPA·H 2 O did not precipitate and remained in the mother liquor.…”
Section: Resultsmentioning
confidence: 91%
“…Derstine et al have carefully observed that NaCl, which forms during pH adjustment, has a large effect on keeping PMPA in solution. 10 Therefore, in a further experiment, aqueous H 2 SO 4 was used for dealkylation and the pH was adjusted with conc. aqueous NH 3 (25 wt %) in order to see how (NH 4 ) 2 SO 4 formation affects the solubility of PMPA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation